Structure and Floristics of Home Gardens in an Altitudinal Marsh in Northeastern Brazil - Carvalho, Thamires Kelly Nunes; Abreu, Diego Batista de Oliveira; Lucena, Camilla Marques de; Pedrosa, Kamila Marques; Vasconcelos Neto, Carlos Frederico Alves; Alves, Carlos Antônio Belarmino; Félix, Leonardo Pessoa; Florentino, Alissandra Trajano Nunes; Alves, Rômulo Romeu Nóbrega; Andrade, Leonaldo Alves; Lucena, Reinaldo Farias Paiva de (Ethnobotany Research and Applications, 2013)
Home gardens are a traditional land use practice, which is very common in the tropics. The main goal of the home garden is to produce food for subsistence purposes. Therefore, they have been considered very important from an economic, cultural and ecological point of view. Despite their importance, there has been a lack in research of these environments in Northeastern Brazil. This research was carried out in a rural community belonging to Areia City (Paraíba, Brazil), and aimed to study the floristic diversity of home gardens and their contribution in the conservation of the local diversity. Semi-structured interviews were conducted, also using the technique of guided tours with the home garden maintainer. At the same time, the yards were measured, as well as all shrubby arboreal individuals present with DGL (diameter at ground level) ≥ 3 cm. A total of 19 yards were analyzed. 177 species were recorded, of which 155 were identified, representing 63 families and 131 genera. Fabaceae (16 spp.), Euphorbiaceae (10 spp.) and Myrtaceae (7 spp.) were the most represented plant families. 94 of the identified species are considered exotic and 83 are native, considering the origin at regional level. Structurally, the home gardens from Vaca Brava community have shown themselves as complex and rich in diversity, as a result of the association of crops and fruit, as well as the presence of native woody plants for which no uses were reported.